IMPLEMENTATION OF THE INNATE IMMUNE RESPONSE IN VIRAL INFECTIONS - Uzokboeva Durdona; Umarova Tamila Abdufattoevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
At the outset, it is necessary to briefly review the main stages of the immune response to viral infections. The human immune system consists of the following components: T- and B-cell branches and factors of nonspecific resistance. The T-cell branch is represented by so-called thymus-dependent CD4+ and CD8+ lymphocytes, which, upon antigenic stimulation, become activated and function as effectors and inducers.